Kepuasan, Semangat, dan Motivasi Kerja Guru Sekolah Dasar di Distrik Mindiptana, Selatan Papua - Andreas Au Hurit; Seli Marlina Radja Leba; Basilius Redan Werang (Musamus Journal of Primary Education, 2022)
This study aimed at exploring the job satisfaction of elementary school teachers in Mindiptana district, Papua, and how it affected their morale and motivation. To explore the effect, we used a quantitative approach using survey research design. This study was guided by the following two research questions, namely: (a) does teachers’ job satisfaction have a significant positive effect on teachers’ morale at elementary schools in Mindiptana district, Southern Papua?, and (b) does teachers’ job satisfaction have a significant positive effect on teachers’ motivation at elementary schools in Mindiptana district, Southern Papua? Three quantitative questionnaires were distributed to 63 teachers. Statistical analysis was performed using the Statistical Package for the Social Sciences (SPSS) version 21 for Windows and a simple linear regression analysis technique. The result revealed that elementary school teachers’ morale and motivation were predicted significantly positively by their job satisfaction. This research finding might be a critical note for education officials of Boven Digoel Regency to take strategic steps to enhance teachers’ morale and teachers’ motivation by creating a program to enhance teachers’ job satisfaction.